2005
DOI: 10.1128/iai.73.1.226-234.2005
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes Involved in Anaerobic Respiration Appear To Play a Role inActinobacillus pleuropneumoniaeVirulence

Abstract: Actinobacillus pleuropneumoniae, the etiological agent of porcine pleuropneumonia, is able to survive on respiratory epithelia, in tonsils, and in the anaerobic environment of encapsulated sequesters. It was previously demonstrated that a deletion of the anaerobic dimethyl sulfoxide reductase gene (dmsA) results in attenuation in acute disease (N. Baltes, S. Kyaw, I. Hennig-Pauka, and G. F. Gerlach, Infect. Immun. 71:6784-6792, 2003). In the present study, using two-dimensional polyacrylamide gel electrophores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 51 publications
6
67
0
Order By: Relevance
“…A significantly higher level of resistance to tetracycline was observed in Spain 85% (14) as well as in Australia 75% (9). Higher levels of resistance of 88.4% and 90.7% for chlortetracycline and oxitetracycline, respectively, were identified in Canada (17). When compared with our previous results (34), we observed a significant decrease in thetetracycline resistance from 53% to 34% as well as in trimethoprim/sulfamethoxazole resistance from 56% to 24%.…”
Section: Methodssupporting
confidence: 45%
See 2 more Smart Citations
“…A significantly higher level of resistance to tetracycline was observed in Spain 85% (14) as well as in Australia 75% (9). Higher levels of resistance of 88.4% and 90.7% for chlortetracycline and oxitetracycline, respectively, were identified in Canada (17). When compared with our previous results (34), we observed a significant decrease in thetetracycline resistance from 53% to 34% as well as in trimethoprim/sulfamethoxazole resistance from 56% to 24%.…”
Section: Methodssupporting
confidence: 45%
“…Multidrug resistance of A. pleuropneumoniae strains has also been registered in other regions of the world. For example, in Canada five isolates demonstrated multidrug resistance to penicillins, streptomycin, tetracyclines and sulfanomides, whereas three others showed multiresistance to streptomycin, sulfonamides and tetracyclines (17). In many countries different levels resistance of A. pleuropneumoniae (10,14,25,30) have been determined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used aerobiosis as it is the typical atmosphere used in experiments involving A. pleuropneumoniae and anaerobiosis as, based on mutant Jacobsen et al 2005;Buettner et al 2009) or transcriptome (Deslandes et al 2010;Klitgaard et al 2012) studies, it is representative of the growth conditions found in necrotic lungs of pigs. As shown in Figure 4 and Table 1, some trans-acting sRNA candidates, like Arrc05 and Arrc08, are located between genes within operons, which could allow them to be mistaken for subproducts of polycistronic mRNA maturation.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that RTX (repeats in toxin) toxins, lipopolysaccharide, capsule, and various amino acid and iron transport systems of the bacterium are essential to cause acute disease [2,6,15,16]. In this study, we identified a new outer membrane protein from a genomic library of A. pleuropneumoniae serotype 7.…”
Section: Discussionmentioning
confidence: 94%